A Validated Method for the Screening of 320 Forensically Significant Compounds in Blood by LC/QTOF, with Simultaneous Quantification of Selected Compounds. Issue 4 (10th January 2018) - Partridge, Emma; Trobbiani, Stephen; Stockham, Peter; Scott, Timothy; Kostakis, Chris
Abstract: A broad drug screening method for toxicologically significant drugs and metabolites in whole blood using liquid chromatography time-of-flight mass spectrometry (LC/QTOF) was developed and comprehensively validated. The method qualitatively screens for 320 compounds while simultaneously quantifying 39. Compounds were extracted from the blood using alkaline liquid/liquid extraction and chromatographic separation was achieved in 12 min. The QTOF was operated using positive mode electrospray ionization using data dependent acquisition. Qualitative validation was performed for all 320 compounds, and included selectivity, recovery, limit of detection, matrix effects, carryover and extract stability. The limits of detection were in the low to sub ng/mL range for the majority of compounds. Full quantitative validation was performed for 39 compounds and accuracy and precision were within 15 and 18%, respectively. The qualitative data processing method uses an in-house retention time, accurate mass and MSMS spectral database, which can be easily updated with new compounds of interest as they emerge onto the market, without affecting method performance. The use of a non-targeted data acquisition method coupled with targeted data processing has proven to be a highly versatile, efficient and robust approach to screening, well suited to meet the needs of the modern toxicology laboratory involved in systematic toxicological analysis.